Adhesive for improving first effect and circulation of silicon negative electrode system battery cell and battery using adhesive

Through the combination of AA, AA and HEA monomers, an adhesive adapted to the volume expansion of silicon negative electrodes is constructed, which solves the problem of poor stability of silicon negative electrodes during the cycle of lithium-ion batteries, and improves the cycle and first-effect performance of the battery.

CN119264841APending Publication Date: 2025-01-07TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411377744.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of volume expansion of silicon negative electrodes during the cycle of lithium-ion batteries, resulting in poor battery stability and insufficient adaptability of commonly used adhesives such as polyvinylidene fluoride and polyacrylic acid in silicon electrode applications.

Method used

Through the mutual combination of AA monomer, AA-like monomer and HEA monomer, an adhesive with strong bonding ability and adapts to the volume expansion of silicon negative electrode is constructed, which is used to improve the first effect and cycle of silicon negative electrode system battery cells. performance.

Benefits of technology

By building a three-dimensional network structure, this adhesive improves ion conduction performance, flexibility and self-healing performance, effectively inhibits the expansion of silicon negative electrode, and improves the cycle stability and first-term effect of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264841A_ABST
    Figure CN119264841A_ABST
Patent Text Reader

Abstract

The invention discloses a battery using an adhesive for improving the first effect and circulation of a silicon negative electrode system cell, the adhesive is formed by polymerizing acrylic acid, quasi-acrylic acid and hydroxyethyl acrylate monomer, the hydroxyethyl acrylate monomer accounts for 1.5-3% of the total mass of the monomer, the acrylic acid monomer accounts for 16-58% of the total mass of the monomer, and the acrylic acid monomer accounts for 0.5-1.5% of the total mass of the monomer. The content of the acrylic monomer is 40-82%, the hydroxyethyl acrylate monomer is located in the middle of the polymer, the structural formula of the acrylic monomer is as follows: # imgabs 0 # R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxyl and phenyl, R3 is selected from any one of cyano and # imgabs 1 #, R4 is selected from one or more of C1-C6 alkoxy, hydroxyl, amino, ester group, acylamino, chloroformyl and acyloxy, and n is 1-3. And R5 is selected from any one of H, carboxyl, hydroxyl, methoxyl and phenyl. The adhesive provided by the invention is strong in adhesive capacity, good in adaptability to volume expansion of a silicon negative electrode, and capable of effectively improving the cycle and the first effect of the battery, and is applied to the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to an adhesive for improving the initial efficiency and cycle of a silicon negative electrode system battery cell and a battery using the adhesive. Technical Background

[0002] For lithium-ion batteries, due to the extremely high theoretical capacity of silicon-based materials (4200mAhg -1 ), silicon-based materials are considered to be one of the most promising high-capacity negative electrode materials. However, the volume of silicon negative electrode will expand and cause powdering during the lithiation / desulfurization cycle, which will affect the formation of solid-electrolyte interface (SEI), and ultimately lead to poor stability during long-term cycling. For decades, in order to solve this problem, researchers have developed many nanostructured silicon, silicon composite materials and suitable electrolytes, but it is still difficult to solve the problem of silicon negative electrode expansion. In batteries, in addition to active materials and electrolytes, negative electrode binders also play an important role in electrochemical systems. Binders can firmly bond negative electrode active materials to current collectors to ensure that the electrode maintains structural integrity during charging and discharging. However, the polyvinylidene fluoride (PVDF) binder commonly used in production currently usually achieves bonding between negative electrode current collectors and negative electrode active materials through van der Waals forces. When used for silicon electrodes, PVDF is often difficult to adapt to the huge expansion of silicon volume during repeated charging and discharging. In contrast, polyacrylic acid (PAA), which constructs hydrogen bonds through carboxylic acid groups to construct strong interactions between Si particles and current collectors, has more advantages. However, the strong brittleness and poor stretchability of PAA at room temperature seriously affect the application of PAA as a binder. At the same time, although there are some adhesives with higher viscosity, they are poorly adaptable to the volume expansion phenomenon in the cycle of silicon negative electrodes, and often cannot contribute to electrochemical performance. Therefore, there is an urgent need for an adhesive with strong bonding ability, good adaptation to volume changes in the cycle of silicon negative electrodes, and can effectively improve battery cycles and first-effect adhesives. Summary of the invention

[0003] In view of the problems in the prior art, the present invention utilizes the mutual compounding effect between AA monomers, AA-like monomers and HEA monomers to construct an adhesive with strong bonding ability, good adaptability to the volume expansion of silicon negative electrodes, and the ability to effectively improve battery cycle and first efficiency, and applies it to batteries.

[0004] The present invention provides an adhesive for improving the first effect and cycle of a silicon negative electrode system battery cell. The adhesive is a polymer formed by polymerizing an AA (acrylic acid) monomer, a quasi-AA monomer, and a HEA (hydroxyethyl acrylate) monomer. The content of the HEA monomer in the total mass of the monomer is 1.5%-3%, the content of the AA monomer in the total mass of the monomer is 16%-58%, the content of the quasi-AA monomer in the total mass of the monomer is 40%-82%, and the HEA is located in the middle of the polymer (i.e., not at the end of the polymer). The structural formula of the quasi-AA monomer is,

[0005] R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy and phenyl, and R3 is selected from cyano, any one of the following, R4 is selected from one or more of C1-C6 alkoxy, hydroxyl, amino, ester, amide, chloroformyl, acyloxy, and R5 is selected from any one of H, carboxyl, hydroxyl, methoxy, and phenyl.

[0006] As some preferred solutions, in the AA-like monomer, R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy, and benzene ring, and R3 is selected from CN or R4 is selected from any one of C1-C4 alkoxy, amino, and amide, the mass content of the HEA monomer is 2%-3%, the content of the AA monomer in the total mass of the monomer is 30%-55%, and the content of the AA-like monomer in the total mass of the monomer is 42%-68%.

[0007] As a further solution, the AA-like monomer may be one or more.

[0008] As a further solution, the weight average molecular weight of the polymer constituting the adhesive is 3 million to 8.5 million.

[0009] As a further solution, the weight average molecular weight of the polymer constituting the adhesive is 5 million to 7 million.

[0010] Based on the adhesive used to improve the first efficiency and cycle of silicon negative electrode system battery cells, we also proposed a battery that is matched with the adhesive to obtain better effects, including an adhesive used to improve the first efficiency and cycle of silicon negative electrode system battery cells.

[0011] As a further solution, the battery is selected from any one of a soft-pack battery, a cylindrical battery, and a square battery, preferably a soft-pack battery.

[0012] As a further solution, the battery also includes a silicon-containing negative electrode sheet.

[0013] As a further solution, the silicon content in the silicon-containing negative electrode sheet is selected from 4%-35%.

[0014] As a further solution, the rolling thickness is 117 μm-145 μm.

[0015] As a further solution, the coating surface density is 170g / m 2 -210g / m 2 .

[0016] As a further solution, the silicon-containing negative electrode sheet also includes a negative electrode active material.

[0017] As a further solution, the negative electrode active material is selected from any one of carbon materials, silicon-containing materials, and metal materials.

[0018] As a further solution, the negative electrode active material is selected from silicon-containing materials.

[0019] As a further solution, the silicon-containing material is selected from any one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0020] As a further solution, the silicon-containing negative electrode sheet also includes a negative electrode current collector and a conductive agent.

[0021] As a further solution, the negative electrode current collector is at least one metal foil layer selected from aluminum, nickel, tin, copper and stainless steel.

[0022] As a further solution, a coating is provided on the surface of the negative electrode current collector.

[0023] As a further embodiment, the coating element of the coating is selected from at least one of carbon element, oxide of coating element, hydroxide of coating element, oxyhydroxide of coating element, carbonate or nitrate or phosphate or borate of coating element, hydroxycarbonate of coating element.

[0024] As a further solution, the negative electrode current collector is preferably a copper foil with a tensile strength of ≥600 MPa, and the coating element is a carbon element.

[0025] As a further solution, the type of the conductive agent is not limited.

[0026] As a further solution, the battery further includes a separator.

[0027] As a further solution, adhesive layers are provided on both side surfaces of the diaphragm.

[0028] As a further solution, a coating is provided on a selected surface of the diaphragm.

[0029] As a further solution, the battery is also provided with an electrolyte and a positive electrode sheet.

[0030] As a further solution, the electrolyte includes an electrolyte, an additive, and a solvent.

[0031] As a further solution, the electrolyte salt is selected from at least one of borates, phosphates and sulfates.

[0032] As a further solution, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.

[0033] As a further solution, the solvent is selected from at least one of a linear carbonate solvent, a carboxylate solvent, and a phosphate solvent.

[0034] As a further solution, the positive electrode sheet includes a positive electrode active material and a positive electrode current collector.

[0035] As a further embodiment, the positive electrode active material includes a positive electrode active substance, a positive electrode binder and a positive electrode conductor.

[0036] As a further solution, the positive electrode active material is not limited, and technicians can select corresponding positive electrode active materials according to needs.

[0037] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0038] As a further solution, the positive electrode conductor is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.

[0039] As a further solution, the adhesive for improving the first effect and cycle of silicon negative electrode system cells is prepared by the following method:

[0040] S1: Dissolve all HEA monomers, part of AA monomers, alkali, and part of AA-like monomers in a solvent in an inert atmosphere according to a stoichiometric ratio;

[0041] S2: adding part of AA-like monomers at 50° C.-80° C. for reaction for 0.5 h-1.5 h, adding an initiator to obtain a mixed solution;

[0042] S3: adding the remaining AA monomer and AA-like monomer to the mixed solution at 60° C.-90° C., reacting and adjusting the pH, and obtaining a binder after dilution.

[0043] As a further solution, in the preparation method, the AA-like substances are preferably two types: propionamide and acrylonitrile, and the mass ratio of propionamide (AM) to acrylonitrile (AN) is 1:2.5-1:3.5.

[0044] As a further solution, the inert atmosphere in step S1 is selected from any one of nitrogen and argon.

[0045] As a further solution, the flow rate of the inert atmosphere in step S1 is selected from 500 mL / min-1 L / min.

[0046] As a further solution, the base in step S1 is selected from any one of a solid base and an aqueous solution of a solid base.

[0047] As a further solution, the solid base in step S1 is selected from any one of NaOH, KOH, LiOH, Ca(OH)2, Mg(OH)2, Na2CO3, and NaHCO3.

[0048] As a further solution, the concentration of the aqueous solution of the solid alkali in step S1 is selected from 5% to 15%.

[0049] As a further solution, in step S1, the mass ratio of AA monomer, alkaline solution and AA-like monomer is 5:2:3-25:10:9.

[0050] As a further solution, the type AA in step S1 is preferably acrylamide AM.

[0051] As a further solution, the solvent in step S1 is selected from one or more of ethanol, acetone or deionized water, preferably deionized water.

[0052] As a further solution, the volume of the solvent in step S1 is selected from 50-350 mL.

[0053] As a further solution, the AA-like monomer in step S2 is preferably AN.

[0054] As a further solution, in step S2, the mass ratio of the AA-type monomer to the initiator is 10:1-30:1.

[0055] As a further solution, the initiator in step S2 is selected from any one of ammonium persulfate, benzoyl peroxide, diisopropylbenzene peroxide, methyl ethyl ketone peroxide, and tert-butyl peroxide.

[0056] As a further solution, the initiator in step S2 is selected from ammonium persulfate.

[0057] As a further solution, in step S3, the mass ratio of AA monomer to AA-like monomer is 1:1-1:7.

[0058] As a further solution, the AA-like monomers in step S3 are preferably AM and AN, and the mass ratio of AM to AN is 1:2.5-1:3.5.

[0059] As a further solution, the dropping time in step S3 is selected from 2.5-5h.

[0060] As a further solution, the reaction time in step S3 is selected from 7-13 h.

[0061] As a further solution, in step S3, any one of NaOH, KOH and LiOH strong alkali aqueous solutions is used to adjust the pH.

[0062] As a further solution, the concentration of the strong alkali aqueous solution in step S3 is selected from 10% to 20%.

[0063] As a further solution, the pH in step S3 is adjusted to 7-8.

[0064] As a further solution, the diluent used for dilution in step S3 is selected from deionized water.

[0065] As a further solution, the solid content of the diluted binder in step S3 is selected from 4% to 20%.

[0066] Compared with the prior art, the present invention has at least the following beneficial effects:

[0067] The adhesive for improving the first efficiency and cycle of silicon negative electrode system cells provided by the present invention has excellent ion conductivity through the introduction of AA monomers, and utilizes the compounding of quasi-AA and AA to achieve the ion conductivity of the adhesive while improving the bonding ability and flexibility of the adhesive, effectively inhibiting the high system expansion of the silicon negative electrode, and further utilizing the compounding effect of AA, quasi-AA and HEA monomers to further improve the self-healing performance of the adhesive, and achieve strong adaptability to the expansion of the silicon negative electrode system, thereby obtaining an adhesive that can effectively inhibit the expansion of the silicon negative electrode and provide ion conductivity, and after the adhesive is applied to the battery, the cycle, first efficiency and capacity density of the battery can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0069] Figure 1 It is the first effect line graph of the battery of Examples 1-10 and Comparative Examples 1-12;

[0070] Figure 2 It is a line graph of the battery peeling force of Examples 1-10 and Comparative Examples 1-12;

[0071] Figure 3 It is a line graph of battery cohesion of Examples 1-10 and Comparative Examples 1-12;

[0072] Figure 4 The pole piece of Example 1 is disassembled;

[0073] Figure 5 This is the disassembled state of the pole piece of comparative example 3.

[0074] For ease of understanding, the adhesive for improving the first efficiency and cycle of silicon negative electrode system cells of the present invention will be described in more detail below, and embodiments of the present invention will be given, but the scope of the present invention is not limited thereby.

[0075] In order to solve the problem of poor battery stability caused by expansion of silicon negative electrode during the cycle, the present invention proposes an adhesive for improving the first effect and cycle of silicon negative electrode system battery cells, wherein the adhesive is a polymer formed by polymerization of AA (acrylic acid) monomer, AA-like monomer and HEA (hydroxyethyl acrylate) monomer, wherein the content of HEA monomer in the total mass of monomers is 1.5%-3%, the content of AA monomer in the total mass of monomers is 16%-58%, the content of AA-like monomer in the total mass of monomers is 40%-82%, and HEA is located in the middle of the polymer (i.e., not at the end of the polymer), wherein the structural formula of the AA-like monomer is,

[0076] R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy and phenyl, and R3 is selected from cyano, any one of the following, R4 is selected from one or more of C1-C6 alkoxy, hydroxyl, amino, ester, amide, chloroformyl, acyloxy, and R5 is selected from any one of H, carboxyl, hydroxyl, methoxy, and phenyl.

[0077] In the adhesive, the presence of AA monomers with carboxylate ions and hydrogen ions makes the adhesive have good ion conductivity. On this basis, the presence of carboxyl groups in AA monomers also gives the adhesive a certain self-healing property. However, PAA is usually brittle and has poor stretchability at room temperature. Therefore, AA-like monomers are also introduced into the adhesive; the introduction of AA-like monomers helps to construct a three-dimensional network structure to improve the stretchability of PAA at room temperature; at the same time, the presence of AA-like monomers also helps to construct polymers with long-chain structures to enhance the flexibility of polymers. During the cycle, the adhesive with a three-dimensional network and a long-chain structure can serve as a buffer layer, effectively improving the adaptability to the expansion of the silicon negative electrode. Furthermore, the construction of a three-dimensional network structure also helps to optimize the ion transmission path, thereby improving the battery's first efficiency and cycle performance. However, although the presence of AA monomers gives the adhesive a certain self-healing ability, However, the mechanical fracture caused by the three-dimensional network structure constructed by AA and AA-like monomers during the cycle is still difficult to repair. Therefore, HEA monomers are further introduced on the basis of AA monomers with carboxylic acid groups. HEA monomers have a unique structure with coexisting carboxylic acid ester groups, double bonds and hydroxyl groups. The structure with coexisting three functional groups can effectively optimize the three-dimensional network structure sites and relieve expansion stress. In addition, the suitable chain length and structure of HEA enable it to combine with AA and AA-like monomers to construct a three-dimensional network with higher adhesion and flexibility. On the basis of further enhancing the flexibility and ductility of the adhesive, we also use the -OH functional group in the HEA monomer to give the adhesive a stronger self-healing ability. Through the mutual compounding of AA monomers, AA-like monomers and HEA monomers, we have obtained an adhesive with high adhesion and self-healing in the silicon negative electrode system, and can significantly improve the first efficiency and cycle performance of the battery.

[0078] The mass content of AA monomer, AA-like monomer and HEA monomer in the total monomer will also affect the bonding and conductivity of the binder. When the mass content of HEA monomer is higher than 3%, the excess HEA monomer may not only lead to uneven curing, but also cause the degree of cross-linking to decrease during the polymerization of the binder, destroy the ideal cross-linking structure, and thus weaken the self-healing ability that depends on the cross-linking framework. When the mass content of HEA is lower than 1.5%, insufficient HEA monomer may cause the binder to be unable to obtain sufficiently strong self-healing properties, making it difficult for the binder to adapt to the expansion of the silicon negative electrode during the cycle. In addition, when the AA monomer content is less than 16%, it may not be able to provide sufficient ion conductivity for the binder, and greater than 58% means that the AA-like monomer or HEA monomer is insufficient, which may lead to the inability to form a stable and self-healing three-dimensional network structure. When the AA-like monomer is greater than 82%, on the one hand, it may lead to weak ion conductivity of the binder, and at the same time, it may cause excessive cross-linking, making it difficult to adapt to the expansion of the silicon negative electrode, affecting the bonding effect of the binder.

[0079] The AA monomer or / and AA-like monomer located at the end of the polymer can effectively construct a uniform three-dimensional network structure, providing a stable framework support for the self-healing repair of the HEA monomer during the later battery cycle expansion; when the HEA monomer is located at both ends, the HEA monomer may not be able to obtain sufficient support from the three-dimensional framework constructed by the AA-like monomer and the AA monomer during the self-healing process, which may not only lead to a decrease in self-healing performance, but also may cause the three-dimensional network structure after self-healing to be insufficiently stable, thereby resulting in a poor bonding effect. Therefore, when the HEA monomer is not located at the end of the adhesive, better bonding and self-healing effects can be obtained.

[0080] As some preferred solutions, in the AA-like monomer, R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy, and benzene ring, and R3 is selected from CN or R4 is selected from any one of C1-C4 alkoxy, amino, and amide, the mass content of the HEA monomer is 2%-3%, the content of the AA monomer in the total mass of the monomer is 30%-55%, and the content of the AA-like monomer in the total mass of the monomer is 42%-68%.

[0081] As a further solution, the AA-like monomer may be one or more.

[0082] As a further solution, the weight average molecular weight of the polymer constituting the adhesive is 3 million to 8.5 million.

[0083] As a further solution, the weight average molecular weight of the polymer constituting the adhesive is 5 million to 7 million, which helps to construct a three-dimensional framework and an adhesive with better bonding ability.

[0084] Based on the adhesive used to improve the first efficiency and cycle of silicon negative electrode system battery cells, we also proposed a battery that is matched with the adhesive to obtain better effects, including an adhesive used to improve the first efficiency and cycle of silicon negative electrode system battery cells.

[0085] As a further solution, the battery is selected from any one of a soft-pack battery, a cylindrical battery, and a square battery, preferably a soft-pack battery.

[0086] As a further solution, the battery also includes a silicon-containing negative electrode sheet.

[0087] As a further solution, the silicon content in the silicon-containing negative electrode sheet is selected from 4%-35%.

[0088] As a further solution, the rolling thickness is 117 μm-145 μm.

[0089] The rolling process increases the density of the electrode sheet by compacting the electrode material. When the axial pressure thickness is less than 117μm, the pores in the electrode material will be compressed, resulting in a decrease in porosity, hindering the penetration of the electrolyte, making the ion conduction path narrow and tortuous, thereby increasing the resistance to ion conduction. When the axial pressure thickness is greater than 145μm, the pore structure in the electrode material will be loose and the porosity will be high, but it is easy to cause mechanical damage or detachment of the electrode during use, affecting the stability and life of the electrode. Although this helps the penetration of the electrolyte, controlling the axial pressure thickness to 117μm-145μm helps to obtain better porosity to reduce the conduction resistance and extend the battery cycle life.

[0090] As a further solution, the coating surface density is 170g / m 2 -210g / m 2 .

[0091] The coating surface density indicates the mass of the negative electrode slurry per unit area. A higher coating surface density means more active material mass per unit area and more charge can be stored, thereby increasing the total capacity of the battery. Therefore, when the coating surface density is lower than 170g / m 2 When the coating surface density is higher than 210g / m, the prepared battery may not be able to store enough charge, resulting in a decrease in the total capacity of the battery. At the same time, it may also lead to insufficient adhesive, making the constructed three-dimensional framework fragile and difficult to achieve the target requirements. However, the higher the coating surface density, the better. When the coating surface density is higher than 210g / m 2 , in this system, higher than 210g / m 2 The coating surface density may lead to increased internal stress of the battery and increased heat dissipation difficulties, thus affecting the battery's cycle performance.

[0092] As a further solution, the silicon-containing negative electrode sheet also includes a negative electrode active material.

[0093] As a further solution, the negative electrode active material is selected from any one of carbon materials, silicon-containing materials, and metal materials.

[0094] As a further solution, the negative electrode active material is selected from silicon-containing materials.

[0095] As a further solution, the silicon-containing material is selected from any one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0096] As a further solution, the carbon material in the silicon-carbon composite material is selected from any one or more of graphite, hard carbon, soft carbon, carbon nanotubes, graphene, and activated carbon.

[0097] As a further solution, the silicon oxide has the general formula SiO x, where 0 <x≤2。

[0098] As a further solution, the silicon-containing negative electrode sheet also includes a negative electrode current collector and a conductive agent.

[0099] As a further solution, the negative electrode current collector is at least one metal foil layer selected from aluminum, nickel, tin, copper and stainless steel.

[0100] As a further solution, a coating is provided on the surface of the negative electrode current collector.

[0101] As a further embodiment, the coating element of the coating is selected from at least one of carbon element, oxide of coating element, hydroxide of coating element, oxyhydroxyl of coating element, carbonate or nitrate or phosphate or borate of coating element, and hydroxycarbonate of coating element.

[0102] As a further solution, the negative electrode current collector is preferably a copper foil with a tensile strength ≥600Mpa, and the coating element is a carbon element. The copper foil with a tensile strength ≥600Mpa can effectively reduce the stretching and demolding of the electrode after cycling. At the same time, the presence of the carbon coating layer can improve the overall conductivity of the battery cell and increase the number of cycles.

[0103] As a further solution, the type of the conductive agent is not limited, and technicians can choose according to actual needs, including at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, conductive carbon black and carbon nanofibers.

[0104] As a further solution, the battery further includes a separator.

[0105] As a further solution, the separator is a single-layer or multi-layer film of at least one selected from glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride (PVDF).

[0106] As a further solution, adhesive layers are provided on both side surfaces of the diaphragm.

[0107] As a further solution, the multi-adhesive layer is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0108] As a further solution, the coating is preferably a PVDF coating. The addition of an oil-based PVDF coating can effectively enhance the adhesion of the diaphragm to the negative electrode active material, inhibit the volume expansion of the negative electrode during the cycle, and at the same time restrain the activities of the positive and negative electrodes, thereby preventing problems such as low cell capacity and battery short circuit caused by misalignment and skewness of the positive and negative electrode sheets.

[0109] As a further solution, a coating is provided on a selected surface of the diaphragm.

[0110] As a further solution, the coating is selected from any one of epoxy resin coating, polyurethane coating, acrylic coating, polyester coating, Teflon coating, silicone coating, and ceramic coating.

[0111] As a further solution, the battery is also provided with an electrolyte and a positive electrode sheet.

[0112] As a further solution, the electrolyte includes an electrolyte, an additive, and a solvent.

[0113] As a further solution, the electrolyte salt is selected from at least one of borates, phosphates and sulfates.

[0114] As a further embodiment, the borate is selected from any one or more of lithium boric acid, lithium bis(trifluoromethylsulfonyl)boric acid, lithium bis(oxalato)boric acid, potassium salt, sodium salt, calcium salt and lithium salt of fluoroboric acid.

[0115] As a further solution, the phosphate is selected from any one or more of lithium iron phosphate, lithium hexafluorophosphate, dilithium hydrogen phosphate, lithium monofluorophosphate, and sodium hexafluorophosphate.

[0116] As a further solution, the sulfate is selected from any one or more of lithium sulfate, sodium sulfate, and magnesium sulfate.

[0117] As a further solution, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.

[0118] As a further embodiment, the lithium salt compound is selected from at least one of lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, lithium hexafluorophosphate, lithium difluorosulfonyl imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium chloride.

[0119] As a further embodiment, the nitrile compound is at least one selected from the group consisting of adiponitrile, succinonitrile, hexanetrinitrile, propionitrile, benzonitrile, acetonitrile and isobutyronitrile.

[0120] As a further embodiment, the organosilicon compound is at least one selected from tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(trimethylsilyl)borate, polydimethylsiloxane, and trimethylchlorosilane.

[0121] As a further embodiment, the sultone compound is selected from at least one of 1,3-propane sultone, 1,3-propylene sultone, benzene sultone, cyclohexene sultone, cyclopentene sultone, vinyl sultone, octyl sultone and phenyl sultone.

[0122] As a further embodiment, the sulfate ester compound is selected from at least one of vinyl sulfate, dimethyl sulfate, ethyl sulfate, propylene sulfate, dimethoxyethane sulfate, and methoxysulfate.

[0123] As a further solution, the solvent is selected from at least one of a linear carbonate solvent, a carboxylate solvent, and a phosphate solvent.

[0124] As a further embodiment, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0125] As a further embodiment, the carboxylic acid ester solvent includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, methyl isobutyrate, ethyl butyrate, methyl trimethylacetate and ethyl trimethylacetate.

[0126] As a further embodiment, the phosphate solvent includes at least one of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, triphenyl phosphate, tris(2,2,2-trifluoroethyl)phosphite and ethoxy(pentafluoro)cyclotriphosphazene.

[0127] As a further solution, the positive electrode sheet includes a positive electrode active material and a positive electrode current collector.

[0128] As a further embodiment, the positive electrode active material includes a positive electrode active substance, a positive electrode binder and a positive electrode conductor.

[0129] As a further solution, the positive electrode active material is not limited, and technicians can select corresponding positive electrode active materials according to needs.

[0130] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0131] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene and polypropylene.

[0132] As a further embodiment, the acrylic resin includes at least one of vinyl acrylate resin, methyl acrylate resin, butyl acrylate resin, acrylic styrene resin, acrylate resin, acrylate copolymer resin, acrylic resin, and acrylic emulsion resin.

[0133] As a further solution, the positive electrode conductor is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.

[0134] As a further solution, the carbon material is selected from any one of carbon nanotubes, graphite, graphene, carbon fiber, activated carbon, and Super P.

[0135] As a further solution, the metal material is selected from a single substance or oxide of any one element selected from silver, copper, nickel, cobalt, aluminum, titanium, rhodium and gold.

[0136] As a further solution, the positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.

[0137] As a further solution, the adhesive for improving the first effect and cycle of silicon negative electrode system cells is prepared by the following method:

[0138] S1: Dissolve all HEA monomers, part of AA monomers, alkali, and part of AA-like monomers in a solvent in an inert atmosphere according to a stoichiometric ratio;

[0139] S2: adding part of AA-like monomers at 50° C.-80° C. for reaction for 0.5 h-1.5 h, adding an initiator to obtain a mixed solution;

[0140] S3: adding the remaining AA monomer and AA-like monomer to the mixed solution at 60° C.-90° C., reacting and adjusting the pH, and obtaining a binder after dilution.

[0141] As a further solution, in the preparation method, the AA-like substances are preferably two types: propionamide and acrylonitrile, and the mass ratio of propionamide (AM) to acrylonitrile (AN) is 1:2.5-1:3.5.

[0142] As a further solution, the inert atmosphere in step S1 is selected from any one of nitrogen and argon.

[0143] As a further solution, the flow rate of the inert atmosphere in step S1 is selected from 500 mL / min-1 L / min.

[0144] As a further solution, the base in step S1 is selected from any one of a solid base and an aqueous solution of a solid base.

[0145] As a further solution, the solid base in step S1 is selected from any one of NaOH, KOH, LiOH, Ca(OH)2, Mg(OH)2, Na2CO3, and NaHCO3.

[0146] As a further solution, the concentration of the aqueous solution of the solid alkali in step S1 is selected from 5% to 15%.

[0147] As a further solution, in step S1, the mass ratio of AA monomer, alkaline solution and AA-like monomer is 5:2:3-25:10:9.

[0148] As a further solution, the type AA in step S1 is preferably acrylamide AM.

[0149] As a further solution, the solvent in step S1 is selected from one or more of ethanol, acetone or deionized water, wherein deionized water is preferably used as the solvent because of its good solubility, environmental friendliness, low cost and the fact that it can increase the dispersibility of the components after diluting the monomers to a certain extent.

[0150] As a further solution, the volume of the solvent in step S1 is selected from 50-350 mL.

[0151] As a further solution, the AA-like monomer in step S2 is preferably AN.

[0152] As a further solution, in step S2, the mass ratio of the AA-type monomer to the initiator is 10:1-30:1.

[0153] As a further solution, the initiator in step S2 is selected from any one of ammonium persulfate, benzoyl peroxide, diisopropylbenzene peroxide, methyl ethyl ketone peroxide, and tert-butyl peroxide.

[0154] As a further solution, the initiator in step S2 is selected from ammonium persulfate.

[0155] As a further solution, in step S3, the mass ratio of AA monomer to AA-like monomer is 1:1-1:7.

[0156] As a further solution, the AA-like monomers in step S3 are preferably AM and AN, and the mass ratio of AM to AN is 1:2.5-1:3.5.

[0157] As a further solution, the dropping time in step S3 is selected from 2.5h-5h.

[0158] As a further solution, the reaction time in step S3 is selected from 7h-13h.

[0159] As a further solution, in step S3, any one of NaOH, KOH and LiOH strong alkali aqueous solutions is used to adjust the pH.

[0160] As a further solution, the concentration of the strong alkali aqueous solution in step S3 is selected from 10% to 20%.

[0161] As a further solution, the pH in step S3 is adjusted to 7-8.

[0162] As a further solution, the diluent used for dilution in step S3 is selected from deionized water.

[0163] As a further solution, the solid content of the diluted binder in step S3 is selected from 4% to 20%.

[0164] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0165] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0166] Example 1

[0167] Preparation of adhesive:

[0168] S1: 21 g AA monomer, 8 g 1% NaOH solution, 5 g AM, and 0.96 g HEA were dissolved in deionized water in an argon atmosphere at 500 mL / min;

[0169] S2: Add 10 g AN at 70 °C, react for 1 h, then add 0.5 g ammonium persulfate to obtain a mixed solution;

[0170] S3: At 65°C, acrylic acid, 10g AA monomer, 6g AM, and 20g AN were added dropwise to the mixed solution within 3.5 hours, and the mixture was reacted for 7 hours. A 10% NaOH strong alkali aqueous solution was used to adjust the pH of the mixed solution to 7, and then the mixture was diluted to 6% solid content with deionized water to obtain a binder.

[0171] Preparation of soft pack batteries:

[0172] The soft-pack battery is obtained by configuring positive and negative electrode ingredients, coating, rolling, sheeting, electrode sheet drying, battery cell assembly, battery drying, battery liquid injection, battery formation, battery vacuum sealing and capacity separation.

[0173] Embodiments 2 to 10

[0174] The preparation parameters of Example 1 were changed, and the other parameters were prepared in the same manner as in Example 1 to prepare an adhesive for improving the first efficiency and cycle of silicon negative electrode system batteries. The parameter changes are listed in Table 1.

[0175] Comparative Examples 1-14

[0176] The preparation parameters of Example 1 were changed, wherein, in step S1 of Comparative Example 4, HEA was not added, AA, quasi-AA, and HEA were added in step S3, and the rest was prepared in the same manner as in Example 1 to prepare an adhesive for improving the first efficiency and cycle of silicon negative electrode system batteries. The parameter changes are listed in Table 1.

[0177] Test Method

[0178] (1) Peel force

[0179] 1. Stick a 20mm*100 double-sided tape on the stainless steel plate, with one end flush with the stainless steel plate.

[0180] 2. Cut the electrode to the appropriate size, with a width slightly larger than the double-sided tape at the bottom, align one end with the double-sided tape, and bend the electrode at the other end at an angle of 180°.

[0181] 3. Use paper tape to fix the plastic sheet and the bent pole piece.

[0182] 4. Pull the pressure roller horizontally to make the pole piece and the bottom double-sided tape tightly bonded, and gently pull the plastic sheet by hand to peel off the pole piece and the double-sided tape;

[0183] 5. Use a tensile testing machine to test. Fix the stainless steel to the fixture below the tensile testing machine, fix the upper plastic sheet to the upper hook, adjust the angle, and stretch at a speed of 300mm / min until the pole piece is completely peeled off.

[0184] (2) Cohesion

[0185] 1. Stick a 30mm*100mm double-sided tape on the stainless steel plate, with one end flush with the stainless steel plate.

[0186] 2. Cut the electrode to the appropriate size, with a width slightly larger than the double-sided tape at the bottom, align one end with the double-sided tape, and fit it tightly on the double-sided tape.

[0187] 3. Use 20mm wide transparent tape (double-sided tape is used in this experiment) to stick it on the test surface of the sample, bend the end at an angle of 180°, pull the pressure roller horizontally to make the tape tightly adhere to the electrode. To facilitate tearing off the tape with the tensile machine, stick the end of the tape on the plastic sheet, gently pull the plastic sheet with your hand to peel off the tape and the active material part.

[0188] 4. Use a tensile testing machine to test. Fix the stainless steel to the fixture below the tensile testing machine, fix the upper plastic sheet to the upper hook, adjust the angle, and stretch at a speed of 300mm / min until all the active substances are peeled off.

[0189] (3) Number of loop terminations

[0190] The number of cycles that the battery cell needs to continuously charge and discharge to 80% of the initial capacity.

[0191] (4)Battery initial performance

[0192] Battery first efficiency = (first cycle discharge capacity / charge capacity) × 100%.

[0193] Table 1

[0194]

[0195]

[0196] Table 2

[0197]

[0198]

[0199]

[0200] As can be seen from Table 2, Examples 1-10 as a whole exhibit better adhesion, cycle ability and battery first efficiency than Comparative Examples 1-14.

[0201] From the comparison of Example 1 and Comparative Example 1, it can be seen that when the adhesive for improving the first sale and cycle of the silicon negative electrode system battery cell is not added, the peeling force of Comparative Example 1 is only 7.3N, and the cohesive force is also much lower than 269N of Example 1, indicating that the addition of the adhesive effectively improves the bonding effect in the negative electrode sheet. At the same time, after adding the adhesive of the present invention, the number of cycle termination circles is increased from 314 circles when no addition is made (Comparative Example 1) to 873 circles, and the battery first efficiency is increased from 75.32% to 85.07%, indicating that the addition of the adhesive can effectively improve the battery cycle capacity and the battery first efficiency, solve the problem of poor cyclability of silicon negative electrode system batteries, and further improve the battery first efficiency.

[0202] From Example 1 and Comparative Examples 2-4, it can be seen that AA monomer, AA-like monomer and HEA monomer are essential for exerting the adhesive effect and improving the battery cycle and the first battery effect. In Example 1 and Comparative Example 2, it can be observed that when no AA monomer is added, the peeling force, cohesion and cycle performance are slightly higher than those of Comparative Examples 3-4, but the first battery effect shows a significant decrease. This may be because the introduction of AA monomers with carboxyl groups not only gives the adhesive a certain self-healing property, but also makes the adhesive exhibit good ion conductivity due to carboxylate ions and hydrogen ions. Therefore, when no AA monomer is added, the first effect of Comparative Example 2 is significantly reduced; since the AA monomer is brittle at room temperature, a AA-like monomer is further introduced. From Example 1 and Comparative Example 3, it can be observed that when no AA-like monomer is added, the battery peeling force is slightly higher than that of Comparative Examples 3-4. The force and cohesion are reduced, and the cycle capacity is weakened. This may be because the introduction of AA-like monomers helps to construct a chemically cross-linked three-dimensional framework, improves the flexibility of the adhesive, and solves the problem of high brittleness of PAA at room temperature. In addition, the three-dimensional network framework constructed by AA-like monomers can also help optimize the ion transmission path, thereby improving the first efficiency of the battery; while Example 1 and Comparative Example 4 show the necessity of HEA monomers. When no HEA monomer is added, the battery cycle capacity is significantly reduced. This may be because the presence of -OH groups in the HEA monomers gives the adhesive a stronger self-repairing ability to repair the three-dimensional framework destroyed when the battery silicon negative electrode expands, thereby improving the battery cycle capacity. Therefore, the compounding effect between AA monomers, AA-like monomers and HEA monomers is crucial to exerting the adhesive effect and improving the battery cycle and the first efficiency of the battery.

[0203] From Example 1 and Comparative Examples 5-7, it can be seen that the ratio of AA monomer, AA-like monomer and HEA monomer of the polymerized adhesive is also one of the factors affecting the bonding effect of the adhesive and the first effect of the battery. When the AA monomer content is lower than 16% and the AA-like monomer content is higher than 82% (Comparative Example 5), the bonding ability and cycle performance are reduced, and the first effect is significantly reduced. This may be because insufficient AA monomers weaken the self-healing ability and conductivity of the adhesive, while AA-like monomers higher than 82% may also cause excessive cross-linking; similarly, when the AA monomer content exceeds 58% and the AA-like content is lower than 40% (Comparative Example 6), although the first effect of the battery is highly improved, the bonding ability and cycle ability are simultaneously deteriorated. This may be because insufficient AA-like monomers cannot construct a stable flexible framework, resulting in reduced bonding ability and cycle ability; and from Example 1 and Comparative Example 7, it can be seen that when HEA is higher than 3%, the bonding ability of the adhesive will also be affected and thus affect the battery cycle ability. This may be because excessive HEA monomers may cause uneven curing and destroy the balance of the cross-linking framework, thereby reducing the bonding ability of the adhesive and the battery cycle ability.

[0204] From Example 1 and Comparative Example 8, it can be observed that the HEA monomer is not located at both ends of the polymer during polymerization, which is also one of the conditions for obtaining an adhesive with high adhesion and conductivity. When the HEA monomer is located at both ends (Comparative Example 8), it may not be able to obtain sufficient support from the three-dimensional framework constructed by the AA-like monomer and the AA monomer during the self-healing process, resulting in a deterioration in the self-healing performance and bonding effect. Therefore, when the HEA monomer is not located at the end of the adhesive, better bonding and self-healing effects can be obtained.

[0205] Example 1, Comparative Examples 9-10 demonstrate another interesting factor that affects the performance of batteries using adhesives - axial compression thickness. It can be observed from Comparative Examples 9-10 that when the axial compression thickness is not 117μm-145μm, both the battery cycle and the first efficiency are affected. This may be because, when the axial compression thickness is less than 117μm (Comparative Example 9), the void structure is compressed, the ion conduction resistance increases, and the battery first efficiency is affected; and when the axial compression thickness is greater than 145μm (Comparative Example 10), the pore structure is loose, making the electrode easily damaged during the cycle, thereby reducing the cycle performance. Therefore, ensuring that the axial compression thickness is 117μm-145μm helps to improve the battery cycle and first efficiency.

[0206] From Example 1 and Comparative Examples 11-12, it can be seen that when the coating surface density is less than 170 g / m 2 (Comparative Example 11), insufficient adhesive may lead to the construction of a relatively fragile three-dimensional framework and insufficient self-healing property, resulting in reduced circulation ability and bonding ability, and may also lead to weak charge storage ability, resulting in reduced first efficiency; on the other hand, it can be observed from Example 1 and Comparative Example 12 that when the coating surface density is greater than 210 g / m2 Too thick a coating will increase the internal stress during the cycle, thus affecting the cycle performance. At the same time, a coating higher than 210g / m 2 Although the coating density improves the initial efficiency of the battery, it may also lead to increased heat dissipation difficulties, further affecting the cycle capacity.

[0207] Interestingly, the current collector and the diaphragm are also factors that affect the performance of the battery. From Example 1 and Comparative Example 13, when a copper foil with a strength of ≤400Mpa is used as the current collector, the bonding ability of the adhesive in the battery is significantly reduced, and the cycle capacity and the first effect of the battery are affected. This may be because the copper foil with a strength of ≥600Mpa has a higher compatibility with the adhesive of the present invention than the copper foil with a strength of ≤400Mpa. At the same time, the presence of high-strength carbon-coated copper foil can effectively reduce the extension and demolding of the electrode after the cycle, and the presence of the carbon coating layer can also improve the overall conductivity of the battery cell and increase the number of cycles. In addition, it can be observed from Example 1 and Comparative Example 14 that when a conventional diaphragm is used, the battery bonding ability and cycle capacity are also weakened. This may be because the bonding diaphragm helps to assist the adhesive in achieving bonding between the active material and the current collector, avoiding the impact of the diaphragm displacement caused by the cyclic expansion of the silicon negative electrode. Therefore, the use of copper foil with a strength of ≥600Mpa and a bonding diaphragm to prepare a battery can obtain better cycle capacity and first effect.

[0208] In the adhesive, the type of AA-like is also a factor that affects the adhesive performance. It can be seen from Examples 1-4 that compared with Example 2 using BA as the AA-like, and Examples 3 and 4 using only AM or AN, Example 1 using both AM and AN exhibits better bonding ability and circulation ability. This may be because, on the one hand, the presence of CN in AM helps to provide sites for the substitution of HEA, and on the other hand, the amino group in AN helps to control the polymer chain length and cross-linking degree, thereby cooperating with each other to construct an adhesive with a suitable three-dimensional structure.

[0209] It can be observed from Examples 1, 5-6 that when the weight average molecular weight of the polymer is 5 million to 7 million, the adhesive exhibits better peeling force and cohesion, and at the same time, the cycle capacity is also improved. This may be because when the weight average molecular weight of the polymer is 5 million to 7 million, the adhesive has a more suitable chain length, crosslinking degree and three-dimensional structure, which can effectively buffer and disperse the internal stress of silicon negative electrode expansion while timely and effectively repairing the three-dimensional framework, thereby further improving the adhesive ability of the adhesive and the cycle capacity of the battery. Therefore, according to Examples 1, 5-6, the weight average molecular weight of the polymer constituting the adhesive is preferably 5 million to 7 million.

[0210] Examples 7-8 show that when the adhesive of the present invention is applied to a high silicon-silicon oxygen system or a low silicon-silicon oxygen system, the adhesive also exhibits excellent bonding ability, enabling the battery to obtain excellent cycling capacity, indicating that the adhesive of the present invention has excellent versatility for silicon negative electrode systems.

[0211] It can be observed from Examples 1, 9-10 that when the mass content of HEA monomer is 2%-3%, the content of AA monomer in the total mass of monomers is 30%-55%, and the content of AA-like monomer in the total mass of monomers is 42%-68%, the constructed adhesive has better comprehensive ability (Example 1). This may be because when the monomers are kept in the above ranges, it is helpful to construct an adhesive with more reasonable chain length, cross-linking degree and ion conductivity, while ensuring the first effect of the battery, giving the battery excellent cycle performance.

[0212] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. An adhesive for improving the initial efficiency and cycle of a silicon negative electrode system battery, characterized in that: It is polymerized by acrylic acid monomer, acrylic acid-like monomer and hydroxyethyl acrylate monomer, wherein the content of hydroxyethyl acrylate monomer in the total weight of monomer is 1.5%-3%, the content of acrylic acid monomer in the total weight of monomer is 16%-58%, the content of acrylic acid-like monomer in the total weight of monomer is 40%-82%, and the hydroxyethyl acrylate monomer is located in the middle of the polymer, wherein the structural formula of acrylic acid-like monomer is, R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy and phenyl, and R3 is selected from cyano, any one of , R4 is selected from one or more of C1-C6 alkoxy, hydroxyl, amino, ester, amide, chloroformyl, acyloxy, and R5 is selected from any one of H, carboxyl, hydroxyl, methoxy, and phenyl.

2. The adhesive for improving the initial efficiency and cycle of silicon negative electrode system batteries according to claim 1, characterized in that: In the AA-like monomer, R1 and R2 are independently selected from any one of H, carboxyl, hydroxyl, methoxy, and benzene ring, and R3 is selected from CN or R4 is selected from any one of C1-C4 alkoxy, amino, and amide, the mass content of the HEA monomer is 2%-3%, the content of the AA monomer in the total mass of the monomer is 30%-55%, and the content of the AA-like monomer in the total mass of the monomer is 42%-68%; Preferably, the AA-like monomer may be one or more; Preferably, the weight average molecular weight of the polymer constituting the adhesive is 3 million to 8.5 million; Preferably, the weight average molecular weight of the polymer constituting the adhesive is 5 million to 7 million.

3. A battery matched with an adhesive to obtain a better effect, characterized in that: The invention comprises an adhesive for improving the initial efficiency and cycle of a silicon negative electrode system battery cell as described in any one of claims 1 to 2.

4. The battery according to claim 3, characterized in that The battery is selected from any one of a soft-pack battery, a cylindrical battery, and a square battery, preferably a soft-pack battery; Preferably, the battery further comprises a silicon-containing negative electrode sheet and a separator; Preferably, the silicon content in the silicon-containing negative electrode sheet is selected from 4% to 35%; Preferably, the rolling thickness is 117 μm-145 μm, and the coating surface density is 170 g / m 2 -210g / m 2 ; Preferably, the silicon-containing negative electrode sheet further comprises a negative electrode active material; Preferably, the negative electrode active material is selected from any one of carbon materials, silicon-containing materials, and metal materials; Preferably, the negative electrode active material is selected from silicon-containing materials; Preferably, the silicon-containing material is selected from any one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

5. The battery according to claim 3, characterized in that The silicon-containing negative electrode sheet also includes a negative electrode current collector and a conductive agent; Preferably, the negative electrode current collector is at least one metal foil layer selected from aluminum, nickel, tin, copper and stainless steel; Preferably, the surface of the negative electrode current collector is provided with a coating; Preferably, the coating element of the coating is selected from at least one of carbon element, oxide of coating element, hydroxide of coating element, oxyhydroxide of coating element, carbonate or nitrate or phosphate or borate of coating element, and hydroxycarbonate of coating element; Preferably, the negative electrode current collector is preferably a copper foil with a tensile strength of ≥600Mpa, and the coating element is a carbon element; Preferably, the battery further comprises a separator; Preferably, a bonding layer is provided on both side surfaces of the diaphragm; Preferably, the membrane is provided with a coating on its surface.

6. The battery according to claim 3, characterized in that The battery is also provided with an electrolyte and a positive electrode sheet; Preferably, the electrolyte includes electrolyte, additives, and solvent; Preferably, the electrolyte salt is selected from at least one of borates, phosphates and sulfates; Preferably, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds; Preferably, the solvent is selected from at least one of a linear carbonate solvent, a carboxylate solvent, and a phosphate solvent.

7. The battery according to claim 3, characterized in that The positive electrode sheet comprises a positive electrode active material and a positive electrode current collector; Preferably, the positive electrode active material comprises a positive electrode active substance, a positive electrode binder and a positive electrode conductive agent; Preferably, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber; Preferably, the positive electrode conductor is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.

8. A method for preparing an adhesive for improving the first efficiency and cycle of a silicon negative electrode system battery cell according to claim 1, characterized in that: The steps include: S1: Dissolve all HEA monomers, part of AA monomers, alkali, and part of AA-like monomers in a solvent in an inert atmosphere according to a stoichiometric ratio; S2: adding part of AA-like monomers at 50° C.-80° C. for reaction for 0.5 h-1.5 h, adding an initiator to obtain a mixed solution; S3: adding the remaining AA monomer and AA-like monomer to the mixed solution at 60° C.-90° C., reacting and adjusting the pH, and obtaining a binder after dilution.

9. The method for preparing an adhesive for improving the first efficiency and cycle of a silicon negative electrode system battery cell according to claim 8, characterized in that: The AA-like substances are preferably two kinds: propionamide and acrylonitrile, and the mass ratio of propionamide (AM) to acrylonitrile (AN) is 1:2.5-1:3.5; Preferably, the inert atmosphere in step S1 is selected from any one of nitrogen and argon; Preferably, the flow rate of the inert atmosphere in step S1 is selected from 500 mL / min-1 L / min; Preferably, the base in step S1 is selected from any one of a solid base and an aqueous solution of a solid base; Preferably, the solid base in step S1 is selected from any one of NaOH, KOH, LiOH, Ca(OH)2, Mg(OH)2, Na2CO3, and NaHCO3; Preferably, the concentration of the aqueous solution of the solid alkali in step S1 is selected from 5% to 15%; Preferably, in step S1, the mass ratio of AA monomer, base, and AA-like monomer is 5:2:3-25:10:9; Preferably, the class AA in step S1 is preferably acrylamide AM; Preferably, the solvent in step S1 is selected from one or more of ethanol, acetone or deionized water, preferably deionized water; Preferably, the volume of the solvent in step S1 is selected from 50 mL to 350 mL.

10. The method for preparing an adhesive for improving the first efficiency and cycle of a silicon negative electrode system battery cell according to claim 8, characterized in that: In the step S2, the AA-like monomer is preferably AN; Preferably, in step S2, the mass ratio of the AA-like monomer to the initiator is 10:1-30:1; Preferably, the initiator in step S2 is selected from any one of ammonium persulfate, benzoyl peroxide, dicumyl peroxide, methyl ethyl ketone peroxide, and tert-butyl peroxide; Preferably, the initiator in step S2 is selected from ammonium persulfate; Preferably, in step S3, the mass ratio of AA monomer to AA-like monomer is 1:1-1:7; Preferably, the AA-like monomers in step S3 are preferably AM and AN, and the mass ratio of AM to AN is 1:2.5-1:3.5; Preferably, the dropping time in step S3 is selected from 2.5-5h; Preferably, the reaction time in step S3 is selected from 7-13h; Preferably, in step S3, any one of NaOH, KOH and LiOH strong alkali aqueous solutions is used to adjust the pH; Preferably, the concentration of the strong alkali aqueous solution in step S3 is selected from 10% to 20%; Preferably, in step S3, the pH is adjusted to 7-8; Preferably, the diluent used for dilution in step S3 is selected from deionized water; Preferably, the solid content of the diluted binder in step S3 is selected from 4% to 20%.

Citation Information

Cited By

  • Silicon-containing negative pole piece, preparation method thereof and battery

    CN122158484A

  • Silicon-based negative electrode sheet and construction method and application thereof using ammonium phosphate salt additive

    CN122739260A